If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -162 = -2x + 6(4x + 6) Reorder the terms: -162 = -2x + 6(6 + 4x) -162 = -2x + (6 * 6 + 4x * 6) -162 = -2x + (36 + 24x) Reorder the terms: -162 = 36 + -2x + 24x Combine like terms: -2x + 24x = 22x -162 = 36 + 22x Solving -162 = 36 + 22x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-22x' to each side of the equation. -162 + -22x = 36 + 22x + -22x Combine like terms: 22x + -22x = 0 -162 + -22x = 36 + 0 -162 + -22x = 36 Add '162' to each side of the equation. -162 + 162 + -22x = 36 + 162 Combine like terms: -162 + 162 = 0 0 + -22x = 36 + 162 -22x = 36 + 162 Combine like terms: 36 + 162 = 198 -22x = 198 Divide each side by '-22'. x = -9 Simplifying x = -9
| 1.5x+4=x+6 | | y=5+.50*12 | | 4s-37=3 | | -66=3x-2(-3x-12) | | 5g=6-2h | | 3(3x+1)=4(2x+1) | | -2x-89=100+5x | | 3t/4=6 | | 34/3.14= | | -12/5=p | | 2(x+4)-3=7+3x-2 | | -23+10x=8x+17 | | 3xy+4-xy-xy+10+y+5x= | | -7m+13=14m | | 3x-87=33-5x | | 2x=6-8x | | (u+3)*7=16 | | -6=d/18 | | C=(3.14)r | | (x^2)+3z=0 | | 24+m=-93 | | -10x-143=7x+78 | | 32=18 | | x+2=-4-2x | | (x+4)(2x+2)= | | x^2-2x+400=0 | | 25=5+.50x | | (q-3)*2=16 | | 12x-31=38+9x | | 5x+3=-x+21 | | 2x(4x-7)= | | 8+p=9 |